Answer:
250 MAYBE
Step-by-step explanation:
<span><span>
The correct answers are:</span><span>
(1) The vertical asymptote is x = 0
(2) The horizontal asymptote is y = 0
</span><span>
Explanation:</span><span>(1) To find the vertical asymptote, put the denominator of the rational function equals to zero.
Rational Function = g(x) = </span></span>

<span>
Denominator = x = 0
Hence the vertical asymptote is x = 0.
(2) To find the horizontal asymptote, check the power of x in numerator against the power of x in denominator as follows:
Given function = g(x) = </span>

<span>
We can write it as:
g(x) = </span>

<span>
If power of x in numerator is less than the power of x in denomenator, then the horizontal asymptote will be y=0.
If power of x in numerator is equal to the power of x in denomenator, then the horizontal asymptote will be y=(co-efficient in numerator)/(co-efficient in denomenator).
If power of x in numerator is greater than the power of x in denomenator, then there will be no horizontal asymptote.
In above case, 0 < 1, therefore, the horizontal asymptote is y = 0
</span>
Answer:

Step-by-step explanation:
we know that
In an <u><em>Arithmetic Sequence</em></u> the difference between one term and the next is a constant and this constant is called the common difference
we have

Let



The common difference is 
We can write an Arithmetic Sequence as a rule

where
a_n is the nth term
d is the common difference
a_1 is the first term
n is the number of terms
Find the 63rd term of the arithmetic sequence
we have

substitute




The answer is A. -∞ < y < 2
I can’t even see da the dawn question LOL